Methods of computer word formation in the modern Russian language: Способы словообразования в сфере компьютерных неологизмов в современном русском языке (Journal of the College of Languages (JCL), 2021)
This paper discusses the study of computer Russian language neologisms. Problems of studying computer terminology are constantly aggravated by the processes of computer technology that is introduced to all walks of life. The study identifies ways of word formation: the origin of the computer terms and the possibility of their usage in Russian language. The Internet is considered a worldwide tool of communication used extensively by students, housewives and professionals as well The Internet is a heterogeneous environment consisting of various hardware and software configurations that need to be configured to support the languages used. The development of Internet content and services is essential for expanding Internet usage. Some of these improvements include the ability to support multiple languages and provide tools for creating and using multilingual content.АннотацияДанная работа посвящена исследованию неологизмов компьютерной лексики в русском языке. Проблемы изучения компьютерной терминологии постоянно усугубляются процессами проникновения компьютерной техники практически во все сферы деятельности общества.. Мы постараемся выделять способы словообразования: описать компьютерные лексемы по происхождению и возможности адаптации в русском языке .